Hot press-formed steel sheet and hot press-formed member
Patent Information
- Application Number
- CN202511718978.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-11
- Publication Date
- 2026-10-20
AI Technical Summary
然而针对现有的汽车车身用高强钢板,其在使用时为保证材料的利用率,基本不考虑各向异性对其性能带来的影响,所以由于带状组织导致的不同方向上韧性的差异极有可能导致高强度钢板制成的构件在汽车碰撞时提前失效,危害驾乘人员的安全
[0058]通过上述两个因子共同对合金成分进行选择,本发明提供了一种高碳含量但低合金含量配比的成分,这既削弱了带状组织对韧性的影响,又获得了高的强度,还通过低合金含量降低了钢板成本。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to a steel sheet for hot stamping and a hot stamping formed component. This application is a divisional application, with parent application number 202510454546.2, application date April 11, 2025, and invention title "Steel sheet for hot stamping and hot stamping formed component". Background Technology
[0002] As the automotive industry continues to demand higher safety and lightweight designs, high-strength and tough steel is being used more and more widely in vehicle body structures. This type of steel can effectively absorb energy during a collision, reducing the impact injury to occupants. At the same time, achieving the same safety standards by reducing material thickness can significantly reduce vehicle weight, thereby improving fuel efficiency and reducing carbon emissions, aligning with the automotive industry's strategic goals of lightweighting and sustainable development.
[0003] Hot-stamped steel sheets are common automotive steel sheets. In conventional design, to ensure a tensile strength of 2000 MPa (in the industry, 2000 MPa typically refers to a hot-stamped tensile strength in the range of 1800-2000 MPa), two main measures are taken: firstly, the carbon content is generally increased to above 0.320%; secondly, a large number of alloying elements, such as Mn, Si, Cr, Ni, and Mo, are added during composition design to ensure the hardenability of the steel, thereby obtaining as much martensite as possible in the microstructure after hot stamping. While these measures guarantee strength, they also introduce other problems.
[0004] First, the obtained martensitic structure has a high carbon content. Therefore, compared to the low-carbon martensite in 1500 MPa grade steel plates (which in the industry typically refers to a hot-stamped tensile strength in the range of 1400~1600 MPa), the toughness of steel plates with a tensile strength of 2000 MPa is significantly reduced. This is consistent with the conventional understanding that as the carbon content increases, the hardness and strength of steel increase, but the plasticity and toughness decrease. Second, the high content of alloying elements such as Mn, Si, Cr, Ni, and Mo added to ensure the hardenability of the material causes segregation within the microstructure, leading to the formation of banded structures during the steel plate production process, and ultimately forming carbon and alloy element depletion and enrichment bands within the microstructure. The formation of these banded structures will lead to significant performance differences in the direction of the bands and in the direction perpendicular to the bands. They can also be used to strengthen the properties of materials in a certain direction. For example, Liu L. et al. (Liu L., Yu Q., Wang Z., Ell J., Huang MX, Ritchie RO (2020). Making ultrastrong steel tough by grain-boundary delamination. Science, 368(6497), 1347-1352.) obtained a banded dual-phase structure with high dislocation density of martensite and high mechanical stability of austenite by hot rolling and warm rolling of medium carbon medium manganese steel (Fe-9.95%Mn-0.44%C-1.87%Al-0.67%V) and by cold rolling, which significantly elongated the original austenite grains along the rolling direction and transformed about 50% of the austenite phase into martensite. This resulted in a yield strength of nearly 2000 MPa, a tensile strength of 2144 MPa, and high fracture resistance. However, existing high-strength steel sheets used in automotive bodies, in order to ensure material utilization, largely disregard the impact of anisotropy on performance. Therefore, the differences in toughness in different directions caused by banding can potentially lead to premature failure of components made from high-strength steel sheets during a car collision, endangering the safety of occupants. Furthermore, once banding occurs, it is difficult to completely eliminate in subsequent production. On the one hand, while this existing technology achieves excellent performance after cold rolling, it fails to recognize the adverse effects of banding on toughness after hot stamping at high carbon content. On the other hand, to obtain the aforementioned superior performance, this existing technology employs a special hot-rolling-warm-rolling-cold-rolling process, which makes the process more complex and limits its industrial production.
[0005] Therefore, there is a need to develop a hot-stamped steel sheet suitable for industrial production, which can produce hot-stamped components with high strength and high toughness through conventional hot-stamping processes using conventional production methods. Summary of the Invention
[0006] This invention was made in view of the above-mentioned problems existing in the prior art.
[0007] One of the objectives of this invention is to provide a hot stamping steel sheet that can effectively reduce the formation of banded structures during conventional steel sheet production, thereby enabling the manufacture of hot stamping components that possess both high strength and high toughness.
[0008] To achieve this objective, the present invention discloses a steel sheet for hot stamping, wherein the chemical composition of the steel sheet matrix, by mass percentage, comprises: 0.360%≤C≤0.480%, 0.20%≤Mn≤1.20%, 0.10%≤Si≤0.80%, 0.10%≤Cr≤1.00%, 0.20%≤Al≤0.70%, 0.001%≤B≤0.010%, 0.05%≤V≤0.20%, 0≤Ni≤0.40%, 0≤P≤0.020%, 0≤N≤0.010%, 0≤ S≤0.010%, 0≤Mo≤0.15%, 0≤W≤0.20%, 0≤Cu≤0.20%, 0≤Co≤0.50%, 0≤Ti≤0.100%, 0≤Nb≤0.100%, 0≤Ta≤0.10%, 0≤Sn≤0.05%, 0≤Sb≤0.05%, 0≤As≤0.05%, 0≤Mg≤0.010%, 0≤Ca≤0.010%, 0≤Zr≤0.10%, 0≤O≤0.02%, and 0≤REM≤0.05%, with the balance being Fe and impurities; Among them, the banded structure sensitivity factor of the steel plate matrix F b-s and austenite pre-strain critical cooling rate stability factor F pre-strain The following conditions must be met: (1) When 0.360% ≤ C ≤ At 0.420%, 0.50% ≤ Mn≤1.20%, F b-s ≤2.65 and F b-s ≤9.05-16.92C and F pre-strain ≥2.70; (2) When 0.420% <C ≤ At 0.480%, 0.20% ≤ Mn ≤ 0.50%, F b-s ≤1.75 and F b-s≤18.43-36.15C and F pre-strain ≥2.40; in, F b-s =1.4Mn+1.1Cr+1.4Si+1.3Ni+1.6Mo-0.78Al, F pre-strain =C+2.1(Mn+1.29Cr+0.07Si+0.37Ni+3.28Mo)+0.5Al.
[0009] Optionally, when 0.360% ≤ C ≤ At 0.420%, F b-s ≤8.55-16.92C, further optionally, F b-s ≤8.05-16.92C.
[0010] Optionally, when 0.360% ≤ C ≤ At 0.420%, F b-s ≤2.20, further optionally F b-s ≤1.80.
[0011] Optionally, 0.360% ≤ C ≤ 0.400%, and optionally 0.380%. ≤ C ≤ 0.400%.
[0012] Further, optionally, when 0.360% ≤ C ≤ When the content is 0.420%, 0.25%≤Al≤0.50% or 0.55≤Mn≤1.00%.
[0013] Optionally, when 0.420% <C ≤ At 0.480%, F b-s ≤17.563-36.15C.
[0014] Optionally, when 0.420% <C ≤ At 0.480%, F b-s ≤1.70, further optionally F b-s ≤1.60.
[0015] Optionally, 0.430%≤ C ≤ 0.470%, and optionally 0.440%. ≤ C ≤ 0.470%, and optionally 0.450%. ≤ C ≤ 0.470%.
[0016] Optionally, when 0.420% <C ≤ When the value is 0.480%, 0.45%≤Al≤0.65% or 0.25%≤Mn≤0.46%.
[0017] Optionally, 0.10%≤Si≤0.60%, optionally, 0.15%≤Si≤0.60%, and further optionally, 0.20%≤Si≤0.50%.
[0018] Optionally, 0.20% ≤ Cr ≤ 0.80%, and even more preferably, 0.20% ≤ Cr ≤ 0.60%.
[0019] Optionally, 0.10%≤Ni≤0.30%.
[0020] Optionally, in order to ensure that the average value of the 10 Vickers hardness points of the steel sheet matrix obtained in the hot rolling coiling process does not exceed 350 HV0.3, when 0.360% ≤ C ≤ At 0.420%, hot-rolled and continuously annealed alloying factors F pro =2.1Mn + 1.7Cr + 1.2Ni + 1.1Si + C + 0.9Al ≤ 3.7; when 0.420% <C ≤ At 0.480%, F pro ≤3.2.
[0021] Optionally, Al / C ≥ 0.65, or Al / C ≥ 0.90.
[0022] Optionally, the steel sheet matrix of the hot-stamped steel sheet comprises, by mass percentage, at least one of the following: 0.01%≤Ni≤0.40%, 0.01%≤Mo≤0.15%, 0.001%≤W≤0.20%, 0.001%≤Cu≤0.20%, 0.001%≤Co≤0.50%, 0.001%≤Ti+Nb≤0.100%, 0.001%≤Ta≤0.10%, and 0.001%≤Sn≤0. 0.05%, 0.001%≤Sb≤0.05%, 0.001%≤As≤0.05%, 0.001%≤Mg≤0.010%, 0.001%≤Ca≤0.010%, 0.001%≤Zr≤0.10%, 0.001%≤O≤0.02%, and 0.001%≤REM≤0.05%, and 0.001%≤Mo+W+Cu+Co+Sn+Sb+Ca+Mg+Zr+REM≤0.30%.
[0023] Optionally, the steel sheet matrix of the hot-stamped steel sheet comprises, by weight percentage: 0.360%. ≤ C≤0.480%, 0.20%≤Mn≤1.20%, 0.10%≤Si≤0.80%, 0.10%≤Cr≤1.00%, 0.20%≤Al≤0.70%, 0.001%≤B≤0.010%, 0.05%≤V≤0.20%, 0≤Ni≤0.40%, 0≤Mo≤0.15%, 0.001%≤Ti+Nb≤0.100%, 0.0010≤P≤0.020%, 0.001≤N≤0.010%, 0.001≤S≤0.010%, with the balance being Fe and impurities.
[0024] Optionally, a hot-dip galvanized aluminum alloy pre-plating layer or a zinc alloy pre-plating layer is coated on at least one surface, preferably two surfaces, of the steel plate substrate. Optionally, the thickness of the aluminum alloy pre-plating layer is 5~33 µm.
[0025] Optionally, the degree of segregation of the room temperature microstructure of the steel plate matrix does not exceed grade 2D or 2E in the standard rating chart of GB / T 34474.1-2017.
[0026] Another object of the present invention is to provide a hot-stamped formed component with high strength and high toughness. The hot-stamped formed component is made of the aforementioned hot-stamped steel sheet according to the present invention and includes a component matrix. Since the hot-stamping process does not cause a change in the composition of the steel sheet matrix, the composition of the component matrix of the hot-stamped formed component is consistent with the composition of the steel sheet matrix of the hot-stamped steel sheet from which it is made. Therefore, the above-described limitations on the steel sheet matrix also apply to the component matrix of the hot-stamped formed component.
[0027] The hot-stamped component according to an embodiment of the present invention includes a component matrix, the chemical composition of which, by mass percentage, comprises: 0.360%≤C≤0.480%, 0.20%≤Mn≤1.20%, 0.10%≤Si≤0.80%, 0.10%≤Cr≤1.00%, 0.20%≤Al≤0.70%, 0.001%≤B≤0.010%, 0.05%≤V≤0.20%, 0≤Ni≤0.40%, 0≤P≤0.020%, 0≤N≤0.010%, 0≤ S≤0.010%, 0≤Mo≤0.15%, 0≤W≤0.20%, 0≤Cu≤0.20%, 0≤Co≤0.50%, 0≤Ti≤0.100%, 0≤Nb≤0.100%, 0≤Ta≤0.10%, 0≤Sn≤0.05%, 0≤Sb≤0.05%, 0≤As≤0.05%, 0≤Mg≤0.010%, 0≤Ca≤0.010%, 0≤Zr≤0.10%, 0≤O≤0.02%, and 0≤REM≤0.05%, with the balance being Fe and impurities; Among them, the banded structure sensitivity factor of the steel plate matrix F b-s and austenite pre-strain critical cooling rate stability factor F pre-strain The following conditions must be met: (1) When 0.360% ≤ C ≤ At 0.420%, 0.50% ≤ Mn≤1.20%, F b-s ≤2.65 and F b-s ≤9.05-16.92C and F pre-strain ≥2.70; (2) When 0.420% <C ≤ At 0.480%, 0.20% ≤ Mn ≤ 0.50%, F b-s ≤1.75 and F b-s ≤18.43-36.15C and F pre-strain ≥2.40; in, F b-s =1.4Mn+1.1Cr+1.4Si+1.3Ni+1.6Mo-0.78Al, F pre-strain=C+2.1(Mn+1.29Cr+0.07Si+0.37Ni+3.28Mo)+0.5Al.
[0028] Optionally, when 0.360% ≤ C ≤ At 0.420%, F b-s ≤8.55-16.92C, optionally, F b-s ≤8.05-16.92C.
[0029] Optionally, when 0.360% ≤ C ≤ At 0.420%, F b-s ≤2.20, further optionally F b-s ≤1.80.
[0030] Optionally, 0.360% ≤ C ≤ 0.400%, and optionally 0.380%. ≤ C ≤ 0.400%.
[0031] Further, optionally, when 0.360% ≤ C ≤ When the content is 0.420%, 0.25%≤Al≤0.50% or 0.55%≤Mn≤1.00%.
[0032] Optionally, when 0.420% <C ≤ At 0.480%, F b-s ≤17.563-36.15C.
[0033] Optionally, when 0.420% <C ≤ At 0.480%, F b-s ≤1.70, further optionally F b-s ≤1.60.
[0034] Optionally, 0.430% ≤ C ≤ 0.470%, optionally 0.440% ≤ C ≤ 0.470%, and optionally 0.450%. ≤ C ≤ 0.470%.
[0035] Optionally, when 0.420% <C≤ When the value is 0.480%, 0.45%≤Al≤0.65% or 0.25%≤Mn≤0.46%.
[0036] Optionally, 0.10%≤Si≤0.60%, optionally, 0.15%≤Si≤0.60%, and further optionally, 0.20%≤Si≤0.50%.
[0037] Optionally, 0.20% ≤ Cr ≤ 0.80%, and even more preferably, 0.20% ≤ Cr ≤ 0.60%.
[0038] Optionally, 0.10%≤Ni≤0.30%.
[0039] Optionally, in order to ensure that the average value of the 10 Vickers hardness points of the steel sheet matrix obtained in the hot rolling coiling process does not exceed 350 HV0.3, when 0.360% ≤ C ≤ At 0.420%, hot-rolled and continuously annealed alloying factors F pro =2.1Mn + 1.7Cr + 1.2Ni + 1.1Si + C + 0.9Al ≤ 3.7; when 0.420% <C ≤ At 0.480%, F pro ≤3.2.
[0040] Optionally, Al / C ≥ 0.65, or Al / C ≥ 0.90.
[0041] Optionally, the component matrix of the hot-stamped component comprises, by mass percentage, at least one of the following: 0.01%≤Ni≤0.40%, 0.01%≤Mo≤0.15%, 0.001%≤W≤0.20%, 0.001%≤Cu≤0.20%, 0.001%≤Co≤0.50%, 0.001%≤Ti+Nb≤0.100%, 0.001%≤Ta≤0.10%, and 0.001%≤Sn≤0. 0.05%, 0.001%≤Sb≤0.05%, 0.001%≤As≤0.05%, 0.001%≤Mg≤0.010%, 0.001%≤Ca≤0.010%, 0.001%≤Zr≤0.10%, 0.001%≤O≤0.02%, and 0.001%≤REM≤0.05%, and 0.001%≤Mo+W+Cu+Co+Sn+Sb+Ca+Mg+Zr+REM≤0.30%.
[0042] Optionally, the component matrix of the hot-stamped component comprises, by weight percentage: 0.360%. ≤C≤0.480%, 0.20%≤Mn≤1.20%, 0.10%≤Si≤0.80%, 0.10%≤Cr≤1.00%, 0.20%≤Al≤0.70%, 0.001%≤B≤0.010%, 0.05%≤V≤0.20%, 0≤Ni≤0.40%, 0≤Mo≤0.15%, 0.001%≤Ti+Nb≤0.100%, 0.0010≤P≤0.020%, 0.001≤N≤0.010%, 0.001≤S≤0.010%, with the balance being Fe and impurities.
[0043] Optionally, the hot-stamped component includes a metal plating on at least one surface, preferably both surfaces, of the component substrate. Optionally, the metal plating can be an aluminum-based alloy plating, such as an aluminum-silicon plating, or a zinc-based alloy plating. Optionally, the thickness of the aluminum-silicon plating is 10–50 µm.
[0044] Optionally, when the C content of the matrix of the hot-stamped component is 0.360%~0.420%, its yield strength is not less than 1500 MPa, its tensile strength is not less than 1950 MPa, and its uniform elongation is not less than 5.8%. Further, the planar fracture strain of the hot-stamped component is not less than 0.170. Optionally, the tensile strength of the hot-stamped component is not less than 2000 MPa, further not less than 2050 MPa, and even further not less than 2100 MPa. Optionally, the planar fracture strain of the hot-stamped component is not less than 0.190, further not less than 0.200, further not less than 0.210, and even further not less than 0.220.
[0045] Optionally, when the C content of the matrix of the hot-stamped component is 0.420%~0.480%, its yield strength is not less than 1600 MPa, its tensile strength is not less than 2150 MPa, and its uniform elongation is not less than 5.0%. Further, the planar fracture strain of the hot-stamped component is not less than 0.110. Optionally, the tensile strength is not less than 2200 MPa, further not less than 2250 MPa, and even further not less than 2300 MPa. Optionally, the planar fracture strain of the hot-stamped component is not less than 0.115, and even further not less than 0.118.
[0046] The present invention, with high C content, rationally proportions the alloying elements of hot stamping steel sheets based on the following findings, enabling the preparation of hot stamping components with both high strength and high toughness using conventional industrial production methods.
[0047] Specifically, in the conventional steel production process, the segregation of alloying elements easily leads to the formation of ferrite and pearlite banded structures along the rolling direction, namely, depleted and enriched zones of carbon and alloying elements. During hot stamping, the depleted zones of the banded structure form low-carbon, low-alloy, low-strength, high-toughness martensite, while the enriched zones form high-carbon, high-alloy, high-strength, low-toughness martensite. In other words, the banded structure results in a banded distribution of martensite structure and properties in the hot-stamped components.
[0048] For hot-stamped components with a strength grade of 1500 MPa, the martensitic banded structure formed therein improves toughness in the banded direction. This is because the added carbon content is relatively low, so the toughness of the high-carbon, high-alloy martensite layer formed by segregation within the microstructure does not decrease significantly to the point of being prone to cracking; at the same time, the low-strength, high-toughness martensite and the high-strength, low-toughness martensite form a composite structure, which overall achieves the effect of improving toughness in the banded direction.
[0049] However, the inventors' in-depth research revealed that for hot-stamped components with a strength of 2000 MPa and above, the banded structure reduces toughness in the banded direction, contrary to the aforementioned phenomenon. This is because low-carbon martensite and high-carbon martensite have the same elastic modulus, and therefore, under the same stress, they undergo equal elastic deformation. However, as deformation progresses, the low-carbon martensite yields first, undergoing plastic deformation, which leads to stress-strain distribution between martensite layers. This causes stress concentration in the high-carbon martensite. Since the martensite in hot-stamped components with a strength of 2000 MPa and above already possesses extremely high strength, approaching the limit where martensite toughness decreases sharply, higher-carbon martensite will become extremely tough, undergoing brittle fracture before reaching the 2000 MPa strength level. Therefore, stress concentration in the high-carbon martensite makes the high-carbon martensite layer prone to cracking, resulting in a high stress concentration factor at the crack tip, which in turn causes the tougher low-carbon martensite layer to crack, leading to the fracture of the entire component. Therefore, for hot-stamped components with a strength of 2000 MPa and above, this invention believes that banded structure is an extremely important reason for the reduction in toughness of this high-carbon martensite. Therefore, it proposes to reduce or eliminate banded structure to improve the toughness of hot-stamped components with a strength of 2000 MPa and above.
[0050] To reduce or eliminate the adverse effects of banded structures, high-temperature homogenizing annealing is commonly used in industry to improve the uniformity of alloy element distribution, thus reducing banded structures. For carbon, as an interstitial atom, its diffusion rate is relatively fast during high-temperature annealing, making homogenization easier. However, substitutional atoms, such as manganese, diffuse relatively slowly at high temperatures, and once significant segregation forms, homogenization is difficult to achieve. The most important reason for this segregation is that alloy solute atoms typically accumulate in the last solidified liquid phase during solidification, resulting in a high alloy content in the final solidified region between dendrites. This segregation of alloy solute atoms is difficult to completely homogenize during subsequent processing. Therefore, electromagnetic stirring technology and rolling process control are often used in steel plate production to improve banded segregation. However, these measures only partially alleviate banded structures and do not fundamentally improve segregation through alloy element design, thus failing to mitigate the impact of banded structures on the toughness of hot-stamped components with a strength of 2000 MPa or higher. However, the alloying elements that cause segregation are precisely the fundamental guarantee for hardenability, ensuring a fully martensitic structure after hot stamping. Therefore, the content of segregating alloying elements cannot be easily reduced. The key technical problem this invention aims to solve is how to both weaken the influence of banded structure on the toughness of hot-stamped components and ensure the high strength of the component.
[0051] To address this, the inventors have creatively proposed a method for simultaneously controlling the sensitive factors of banded tissue. F b-s and the critical cooling rate stabilization factor of austenite pre-strain F pre-strain The amount of alloying elements added is strictly controlled. The synergistic effect of these factors balances the influence of alloying elements on toughness and strength, enabling the component to achieve high toughness while maintaining high strength.
[0052] First, in order to control the damage of banded structure to the toughness of hot-stamped components, the inventors proposed a banded structure sensitivity factor. F b-s=1.4Mn+1.1Cr+1.4Si+1.3Ni+1.6Mo-0.78Al (Equation 1). Although Mn, Cr, Si, Ni, Mo, and other alloying elements are known to those skilled in the art as banding-forming elements, the strength of their influence on segregation is unclear, making it impossible to rationally select the proportions of alloying elements. Generally, the segregation of alloying elements is due to the difference in solubility of alloying elements in the liquid and solid phases, leading to a redistribution of alloying elements between the liquid phase and the newly formed solid phase during solidification. Based on this, the inventors input the alloy composition of this invention into the thermodynamic calculation software Thermo-Calc to obtain the corresponding equilibrium phase diagram and the content of each element in the liquid phase and δ-ferrite phase at different temperatures. Then, based on the phase diagram, the temperature corresponding to the maximum δ-ferrite content was found, and the content of each element in the liquid phase at that temperature was compared with the content in the already formed δ-ferrite phase to obtain the influence coefficient of each element on segregation formation, thereby quantitatively clarifying the influence of banding-forming elements Mn, Cr, Si, Ni, and Mo. It is worth noting that this invention considers the effect of Al on segregation because the inventors have found that it has the effect of mitigating the performance degradation caused by segregation. The average banding sensitivity factor for the alloy composition of this invention, calculated from the above theoretical calculations, is [value missing]. F b-s =1.4Mn+1.1Cr+1.4Si+1.3Ni+1.6Mo-0.78Al. Based on the above, the inventors discovered that (1) when 0.360% ≤ C ≤ At 0.420%, F b-s ≤2.65 and F b-s ≤9.05-16.92C; and (2) when 0.420% <C ≤ At 0.480%, F b-s ≤1.75 and F b-sOnly temperatures between 18.43 and 36.15°C can control the banding degree of the annealed or coated microstructure to not exceed grade 2D or 2E in the standard rating chart of GB / T 34474.1-2017. By controlling the banding structure, the heritability of banding structure during hot stamping can be effectively suppressed. In the austenitization stage of hot stamping, heating at ~930°C for only a few minutes results in austenite with a densely packed FCC crystal structure. The diffusion rate of alloying elements in austenite is low, meaning that the initial banding structure cannot achieve sufficient homogenization diffusion of substitutional solid solution atoms such as Mn during austenitization. Usually, this homogenization treatment of alloying elements requires holding at 1100°C or even 1200°C for several hours to tens of hours to achieve homogenization diffusion of substitutional solid solution atoms. However, after heating in the austenitization stage, the microstructure is usually quickly quenched through the die to form martensite after only a few seconds to tens of seconds, which also cannot achieve homogenization diffusion. Therefore, reducing the banded structure in the initial microstructure can effectively alleviate the reduction in toughness caused by the banded distribution in high-carbon hot-stamped components after quenching to martensite in the die. It also effectively improves the reduction in toughness caused by the banded structure in the transverse direction (perpendicular to the banded structure), significantly increasing the material toughness in the direction with the lowest toughness, thus ensuring the safety of the vehicle body in a collision. It will be understood that the fewer alloying elements, the lower the tendency to form banded structures; therefore, when only considering the elimination of banded structures, it is not necessary to set... F b-s The lower limit value. In addition, there are some elements not mentioned in this document but that may cause the formation of banded structures. It will be understood that, in the case of adding these forming elements, the present invention requires that the content of these forming elements be within 0.20% and their total addition amount not exceed 0.50%, so that the addition of these banded structure forming elements does not affect the overall segregation of the steel plate.
[0053] Meanwhile, in order to ensure that the room temperature microstructure of the hot-stamped components contains a sufficient amount of martensite, the inventors proposed a stability factor for the critical cooling rate of austenite pre-strain. F pre-strain= C + 2.1(Mn + 1.29Cr + 0.07Si + 0.37Ni + 3.28Mo) + 0.5Al (Equation 2). A critical cooling rate of 20-30℃ / s is generally sufficient to meet the hardenability requirements of hot-stamped steel sheets in industrial production, ensuring enough martensite within the hot-stamped microstructure to guarantee the performance of the hot-stamped components. However, in cases of deformation, a higher cooling rate is generally considered necessary to obtain sufficient martensite. For the most commonly used 22MnB5 hot-stamped steel, its designed critical cooling rate is approximately 20℃ / s, but when the deformation reaches 5-10%, a cooling rate higher than 50℃ / s is actually required to ensure a fully martensitic microstructure. This is because deformation provides nucleation sites and higher strain-stored internal energy for ferrite phase transformation, thus promoting ferrite phase transformation from both thermodynamic and kinetic perspectives—the well-known strain-induced ferrite phase transformation. The hot stamping steel with a strength of 1700 MPa and above that has been successfully developed and applied also follows the understanding of the hardenability of 22MnB5 hot stamping steel in its design, and its critical cooling rate is designed to be below 20℃ / s to ensure hardenability.
[0054] However, the inventors have found that it is not necessary to design the alloy in this way, because for the hot stamping steel sheet of the present invention with high C content and strength of 1950 MPa and above, the alloy design can ensure hardenability and obtain sufficient martensitic structure without having to meet the critical cooling rate of less than or equal to 20°C / s given by common knowledge, for the following reasons.
[0055] The inventors noted that in hot stamping, the forming process generally occurs in the temperature range of 600-800°C, with a deformation time of only 1-3 seconds. Therefore, the microstructure of the steel sheet during forming remains austenite, and the deformation is austenite plastic deformation. Since the essence of austenite plastic deformation is dislocation slip, this deformation leads to an increase in the dislocation density in austenite, thereby increasing its stored internal energy. In contrast, the stored internal energy of ferrite formed by the austenite phase transformation remains unchanged (due to the absence of dislocations caused by deformation). Therefore, compared to the undeformed state, the energy difference between the deformed austenite and ferrite increases, which enhances the driving force for the austenite phase transformation to ferrite, thus accelerating the phase transformation. However, deformation also leads to the generation of numerous dislocations. Dislocations themselves are line defects that disrupt the integrity of the austenite lattice. At this point, the high-content carbon atoms, which cause the austenite lattice to expand and increase the lattice distortion energy, will spontaneously diffuse to the dislocation lines to reduce the system's free energy, simultaneously forming "Cochrie atmospheres" that significantly pin the dislocations. In this case, theoretical calculations show that, within the range of 600–800℃, assuming a constant temperature for 1–3 seconds during deformation, the diffusion distance of carbon atoms in austenite ranges from 0.7 to 6.7 μm, achieving micrometer-level diffusion. Other alloying elements, such as Mn and Cr, whose substitutional solid solution atoms have lower diffusion rates (usually two orders of magnitude lower than carbon atoms), find it difficult to diffuse to the dislocation lines. Dislocations generated during austenite plastic deformation are difficult to move due to the pinning effect of carbon atoms, and carbon atoms need to overcome even greater resistance to escape the constraints of dislocations and diffuse over long distances. Since the austenite-to-ferrite phase transformation is a diffusion-type phase transformation, which depends on atomic diffusion and is particularly controlled by interfacial carbon diffusion, for hot-stamped steel with high carbon content, the interaction between carbon atoms and dislocations after deformation will not promote the austenite-to-ferrite phase transformation, but will instead kinetically delay its occurrence. This is a finding contrary to common knowledge.
[0056] Based on the above findings, the inventors realized that the austenite-to-ferrite phase transformation during hot stamping is suppressed, which means that the hardenability of the material is guaranteed, and the phase transformation is to martensite. Therefore, for alloy design of steel with high carbon content, the present invention believes that C should also be taken into account when considering hardenability.
[0057] This invention has been proven through numerous experiments that when the carbon content is in the range of 0.360% to 0.480%, the influence of carbon on the static phase transformation is relatively small. However, when the carbon content is in this range, during hot stamping with a pre-strain of 5 to 10%, it can play a significant role in suppressing the occurrence of ferrite phase transformation, thereby ensuring the hardenability of the material. Therefore, when designing steel for hardenability under this carbon content, it is not necessary to adhere to the critical cooling rate of less than or equal to 20℃ / s given by common knowledge. This is because, as explained above, under a pre-strain of 5 to 10%, sufficient martensite structure can still be obtained even when the actual cooling rate is less than 50℃ / s. Therefore, under the high carbon content of 0.360% to 0.480%, considering the influence of other alloying elements on the hardenability of the material, and taking into account that carbon is also an important element for stabilizing the critical cooling rate of austenite pre-strain, the inventors propose (1) when 0.360% ≤ C ≤ At 0.420%, control F pre-strain ≥2.70; and (2) when 0.420% <C ≤ At 0.480%, control F pre-strain ≥2.40. The addition of high carbon content allows for a reduction in the content of alloying elements typically added to ensure the hardenability of the material, enabling the present invention to achieve the expected high strength with reduced alloying elements.
[0058] By selecting alloy composition using the two factors mentioned above, this invention provides a composition with high carbon content but low alloy content ratio. This not only weakens the influence of banded structure on toughness but also achieves high strength, and reduces steel plate cost through low alloy content.
[0059] Optionally, in order to ensure the continuous stability of steel coil production and obtain hot-rolled coils with high stability in both microstructure and properties, this invention further proposes controlling the alloying factor during hot rolling and continuous annealing. F pro=2.1Mn+1.7Cr+1.2Ni+1.1Si+C+0.9Al (Equation 3). In industrial production, the head, tail, and edges of hot-rolled steel coils are in direct contact with the external air medium. Therefore, these parts cool faster than the core of the steel plate during hot rolling and are more susceptible to changes in ambient temperature. This results in a higher proportion of high-hardness martensite phase in the room temperature microstructure of these parts, significantly increasing their strength and hardness. On the one hand, the high strength of the head and tail not only makes uncoiling difficult in subsequent pickling and rolling processes but also causes a sharp increase in rolling force during deformation, affecting production efficiency and leading to problems such as poor plate shape. On the other hand, the high strength of the head and tail also results in significant differences in microstructure and properties between the head / tail and the core after continuous annealing or plating, thus significantly affecting the final yield. Meanwhile, the presence of hard and brittle martensite at the edges of steel coils reduces their deformation capacity, making them prone to edge cracks or even strip breakage during subsequent cold rolling processes. This can affect the production rhythm or even prevent production from proceeding.
[0060] For hot-stamped steel sheets, during continuous annealing production, the steel sheet is typically heated to 740-850°C and held at that temperature for a period of time, then slowly cooled to a temperature above 600°C before being rapidly cooled to 200-400°C for aging treatment. For plating, such as aluminum-silicon coating, the heated steel sheet is slowly cooled to approximately 650°C and coated, then rapidly cooled to below 300°C. Therefore, to ultimately obtain annealed or coated sheets with stable and uniform microstructure and mechanical properties while reducing the scrap rate, the inventors, based on the cooling rate of the head, tail, and edge of hot-rolled steel coils after coiling (between 1-10°C / s), proposed controlling the amount of alloying elements added to further regulate the phase transformation during hot rolling and coiling, thereby reducing its sensitivity to cooling rate and minimizing or avoiding the possibility of high-hardness martensite formation within the microstructure. To achieve this control objective, the inventors proposed hot-rolling and continuous annealing alloying factors. F pro =2.1Mn+1.7Cr+1.2Ni+1.1Si+C+0.9Al, which comprehensively characterizes the influence of alloying elements in steel plates on the austenite transformation during continuous cooling. This invention achieves this through 0.360% ≤ C ≤ At 0.420%, regulation F pro =2.1Mn + 1.7Cr + 1.2Ni + 1.1Si + C + 0.9Al ≤ 3.7; and when 0.420% <C ≤ At 0.480%, regulation F proWith a strength of ≤3.2, the formation of a high proportion of martensite in the microstructure is largely reduced or avoided during continuous cooling. Instead, a microstructure dominated by ferrite and pearlite is obtained, thereby ensuring the continuity of hot stamping steel sheet production and the uniformity and stability of the microstructure and properties of the rolled steel sheet. This reduces or at least alleviates defects such as edge cracking and poor flatness of the coil head and tail after cold rolling, and improves the yield of hot stamping steel sheets.
[0061] Various factors in this invention, for example, F b-s , F pre-strain , F pro In the calculations, each element is calculated using its mass percentage. For example, in Equation 2, 0.5Al, assuming an Al content of 0.40%, is calculated as 0.40, i.e., 0.5Al = 0.5 × 0.40 = 0.20. Those skilled in the art will understand that any range or value within the intervals mentioned herein is applicable to this invention. Attached Figure Description
[0062] Figure 1A and Figure 1B The microstructure and standard rating spectra of the steel substrate samples of aluminum-silicon pre-coated steel sheets of Comparative Example C1 and Example S7 according to the present invention are shown respectively. Figures 2-3 Metallographic images of room temperature microstructures of tensile portions of steel plate S3 and known 22MnB5 specimens after undergoing the same hardenability evaluation test according to an embodiment of the present invention are shown. Figures 4-5 Metallographic images of room temperature microstructures of tensile portions of steel plates HS4 and 22MnB5, according to embodiments of the present invention, after undergoing the same hardenability evaluation test, are shown. Figure 6 The hardness distribution in the thickness direction of the room temperature microstructure of the hot-stamped component obtained by hot stamping from the aluminum-silicon pre-coated steel sheet of Embodiment S7 and Comparative Example C1 according to the present invention is shown. Figure 7A and Figure 7B The carbon content and banding sensitivity factor of hot-stamping steel sheets of grades 2200 MPa and 2400 MPa according to embodiments of the present invention are shown. F b-s Relationship diagram. Detailed Implementation
[0063] The invention will now be described in more detail with reference to exemplary embodiments. All descriptions of chemical element content (%) herein refer to mass percentages. Unless otherwise specified, preferred embodiments can be freely combined as needed. Unless explicitly stated otherwise, all ranges include extreme values. Those skilled in the art will understand that the data and various parameters described in the embodiments are exemplary only and do not constitute a limitation of the invention. It will be understood that 2200 MPa grade typically refers to a hot-stamped tensile strength in the range of 2000-2300 MPa. 2400 MPa grade typically refers to a hot-stamped tensile strength in the range of 2300-2500 MPa. It will be understood that baking the hot-stamped component after hot stamping will reduce the tensile strength by at least 50 MPa. The 0.360% of the present invention will be referred to herein. ≤ C ≤ A steel component with 0.420% steel content in a hot-stamped part is designated as a 2200 MPa grade component. <C ≤ A steel component with 0.480% steel content is classified as a 2400 MPa grade component.
[0064] According to embodiments of the present invention, the steel sheet matrix of the hot-stamped steel sheet comprises, by mass percentage: 0.360%≤C≤0.480%, 0.20%≤Mn≤1.20%, 0.10%≤Si≤0.80%, 0.10%≤Cr≤1.00%, 0.20%≤Al≤0.70%, 0.001%≤B≤0.010%, 0.05%≤V≤0.20%, 0≤Ni≤0.40%, 0≤P≤0.020%, 0≤N≤0.010%, and 0≤S≤0.01%. 0%, 0≤Mo≤0.15%, 0≤W≤0.20%, 0≤Cu≤0.20%, 0≤Co≤0.50%, 0≤Ti≤0.100%, 0≤Nb≤0.100%, 0≤Ta≤0.10%, 0≤Sn≤0.05%, 0≤Sb≤0.05%, 0≤As≤0.05%, 0≤Mg≤0.010%, 0≤Ca≤0.010%, 0≤Zr≤0.10%, 0≤O≤0.02%, and 0≤REM≤0.05%, with the balance being Fe and impurities; Among them, the banded structure sensitivity factor of the steel plate matrix F b-s and austenite pre-strain critical cooling rate stability factor F pre-strain The following conditions must be met: (1) When 0.360% ≤ C ≤ At 0.420%, 0.50% ≤ Mn≤1.20%, F b-s ≤2.65 andF b-s ≤9.05-16.92C and F pre-strain ≥2.70; (2) When 0.420% <C ≤ At 0.480%, 0.20% ≤ Mn ≤ 0.50%, F b-s ≤1.75 and F b-s ≤18.43-36.15C and F pre-strain ≥2.40; in, F b-s =1.4Mn+1.1Cr+1.4Si+1.3Ni+1.6Mo-0.78Al, F pre-strain =C+2.1(Mn+1.29Cr+0.07Si+0.37Ni+3.28Mo)+0.5Al.
[0065] Optionally, at 0.360% ≤ C ≤ At 0.420%, F pro =2.1Mn + 1.7Cr + 1.2Ni + 1.1Si + C + 0.9Al ≤ 3.7; when 0.420% <C ≤ At 0.480%, F pro ≤3.2.
[0066] Optionally, the steel sheet matrix of the hot-stamped steel sheet contains, by weight percentage: 0.360%. ≤ C≤0.480%, 0.20%≤Mn≤1.20%, 0.10%≤Si≤0.80%, 0.10%≤Cr≤1.00%, 0.20%≤Al≤0.70%, 0.001%≤B≤0.010%, 0.05%≤V≤0.20%, 0≤Ni≤0.40%, 0≤Mo≤0.15%, 0≤P≤0.020%, 0≤N≤0.010%, 0≤S≤0.010%, with the balance being Fe and impurities.
[0067] Optional 0.365% ≤C≤0.420%, optionally 0.370%≤C≤0.405%, optionally 0.380%≤C≤0.400%. Optionally 0.55%≤Mn≤1.20%, optionally 0.60%≤Mn≤1.00%, optionally 0.60%≤Mn≤0.85%, optionally 0.75%≤Mn≤1.00%. Optionally 0.10%≤Si≤0.75%, optionally 0.15%≤Si≤0.75%, optionally 0.15%≤Si≤0.65%. Optionally 0.20%≤Al≤0.50%, optionally 0.20%≤Al≤0.45%, optionally 0.20%≤Al≤0.40%. Optionally 0.10%≤Cr≤0.85%, optionally 0.10%≤Cr≤0.65%, optionally 0.25%≤Cr≤0.55%.
[0068] Optional 0.430% ≤ C≤0.470%, optionally 0.440%≤C≤0.470%, optionally 0.450%≤C≤0.470%. Optionally 0.25%≤Mn≤0.50%, optionally 0.25%≤Mn≤0.45%, optionally 0.30%≤Mn≤0.40%. Optionally 0.10%≤Si≤0.60%, optionally 0.15%≤Si≤0.60%, optionally 0.20%≤Si≤0.50%. Optionally 0.35%≤Al≤0.70%, optionally 0.40%≤Al≤0.65%, optionally 0.40%≤Al≤0.60%. Optionally 0.10%≤Cr≤0.85%, optionally 0.10%≤Cr≤0.65%, optionally 0.25%≤Cr≤0.55%.
[0069] Optionally, the steel sheet matrix of the hot-stamped steel sheet comprises, by mass percentage, at least one of the following: 0.01%≤Ni≤0.40%, 0.01%≤Mo≤0.15%, 0.001%≤W≤0.20%, 0.001%≤Cu≤0.20%, 0.001%≤Co≤0.50%, 0.001%≤Ti+Nb≤0.100%, 0.001%≤Ta≤0.10%, and 0.001%≤Sn≤0. 0.05%, 0.001%≤Sb≤0.05%, 0.001%≤As≤0.05%, 0.001%≤Mg≤0.010%, 0.001%≤Ca≤0.010%, 0.001%≤Zr≤0.10%, 0.001%≤O≤0.02%, and 0.001%≤REM≤0.05%, and 0.001%≤Mo+W+Cu+Co+Sn+Sb+Ca+Mg+Zr+REM≤0.30%.
[0070] The hot-stamped forming component according to the present invention is made of the aforementioned hot-stamped forming steel sheet of the present invention. The component matrix of the hot-stamped forming component has the same composition content as the steel sheet matrix of the hot-stamped forming steel sheet used to manufacture it; therefore, the above-mentioned limitation on the steel sheet matrix of the hot-stamped forming steel sheet applies here and will not be repeated.
[0071] The following is an explanation of each element.
[0072] C: 0.360%~0.480% and Mn: 0.20%~1.20% Carbon (C) is an important interstitial solid solution strengthening element in steel, enabling materials to achieve extremely high strength and hardness. Therefore, this patent adds a C content of more than 0.360% to ensure that the hot-stamped components achieve a strength of more than 1950 MPa. However, excessive addition of C increases the phase transformation stress of martensite, promotes the formation of brittle twinned martensite, and severely deteriorates toughness. Therefore, the overall carbon content of this invention is controlled within the range of 0.360% to 0.480%.
[0073] Manganese (Mn) is an effective element for improving the hardenability of steel. When the Mn content is below approximately 0.20%, its improvement on the hardenability of the material is not significant, and it is difficult to ensure that the steel obtains sufficient martensite structure during hot stamping, thus making it difficult to guarantee the high strength and hardness of the material. However, when the Mn content is too high, the material is prone to severe banded segregation, which deteriorates the performance of the steel. At the same time, it promotes the martensitic transformation to occur at lower temperatures, generating brittle twinned martensite, which in turn leads to a decrease in the toughness of the material. In addition, with the increase of Mn content, the thermal conductivity of the steel decreases sharply, and the coefficient of linear expansion increases, resulting in greater internal stress during rapid heating or cooling, and increasing the tendency of parts to crack. Therefore, this invention sets the upper limit of Mn content at 1.20%.
[0074] Through extensive experimentation, the inventors discovered that a high carbon content increases the difficulty of the austenite-to-ferrite phase transformation during hot stamping deformation due to the interaction between carbon and dislocations. In other words, a high carbon content ensures the hardenability of the material. Therefore, in alloy design, the Mn content can be reduced accordingly with increasing carbon content, thereby ensuring hardenability while reducing banded structures caused by Mn segregation. Therefore, in this invention, when 0.360%... ≤ C ≤ At 0.420%, 0.50% ≤ Mn≤1.20%, optionally, 0.55%≤Mn≤1.20%, optionally, 0.60%≤Mn≤1.00%, optionally, 0.60%≤Mn≤0.85%, optionally, 0.75%≤Mn≤1.00%; when 0.420% <C ≤ At 0.480%, 0.20% ≤ Mn≤ 0.50%, optionally, 0.25%≤Mn≤0.50%, optionally 0.25%≤Mn≤0.45%, optionally 0.25%≤Mn≤0.40%.
[0075] Si: 0.10%~0.80% Si can strengthen the matrix through solid solution treatment. It also acts as a deoxidizer in the steelmaking process, thus requiring a content of at least 0.10%. However, excessive Si addition can lead to the formation of difficult-to-remove oxides on the steel surface during production, affecting the surface quality of the final product. Therefore, the upper limit of Si content in this invention is set at 0.80%, optionally not exceeding 0.75%, 0.70%, or 0.65%. Optionally, the Si content is at least 0.20%, 0.30%, or 0.35%.
[0076] Cr: 0.10%~1.00% The Cr content is at least 0.10% to achieve the following effects. First, Cr significantly delays the ferrite-pearlite phase transformation by shifting the isothermal transformation C-curve of steel to the right by hindering the nucleation and growth of cementite. Second, Cr reduces the austenite decomposition rate, lowering the critical cooling rate of the steel and promoting martensite formation. Furthermore, the effect of Cr on reducing the martensite transformation temperature is significantly lower than that of Mn; therefore, Cr is more conducive to promoting the formation of dislocation-type martensite with good toughness. However, excessive Cr addition increases alloy costs and makes it difficult to completely remove the oxide scale formed on the surface of hot-rolled coils through pickling, affecting the surface quality of the final product. Therefore, in this invention, the Cr content is controlled below 1.00%, optionally not exceeding 0.85%, 0.80%, or 0.65%. Optionally, the Cr content is at least 0.20%, 0.30%, or 0.40%.
[0077] Al: 0.20%~0.70% Al atoms have a larger atomic radius than Fe atoms (Al atomic radius: 1.43 * 10⁻⁶). -1 nm, Fe atomic radius: 1.24*10 -1Furthermore, Al (nm) is a substitutional solid solution atom, so the addition of Al can cause the matrix lattice to expand, thus effectively alleviating the lattice distortion caused by interstitial solid solution atoms such as carbon and improving the toughness of martensite. In addition, the addition of Al can combine with N to form AlN, effectively fixing N and preventing the combination of N and B, ensuring that the added B can effectively guarantee hardenability. Therefore, this invention requires an Al content of at least 0.20%. However, if the amount of Al added is too high, it will cause excessive resistance at the crystallizer inlet during continuous casting, affecting billet production. Therefore, the Al content in this invention is controlled between 0.20% and 0.70%, optionally between 0.20% and 0.60%.
[0078] Optionally, Al / C ≥ 0.65 The addition of more than 0.360% C ensures that the hot-stamped components can achieve a target tensile strength of over 1950 MPa. However, the high amount of interstitial solid solution C atoms also causes significant lattice distortion, increasing the brittleness of the martensite formed during hot stamping. As mentioned above, adding Al can expand the crystal lattice, thereby reducing the lattice distortion caused by interstitial solid solution of C atoms and improving the toughness of martensite. Therefore, this invention proposes to add a correspondingly higher content of Al when adding high carbon, thus requiring Al / C ≥ 0.65, optionally Al / C ≥ 0.90, and more preferably Al / C ≥ 1.10.
[0079] B: 0.001%~0.010% Boron readily segregates at austenite grain boundaries, which can suppress the phase transformation from austenite to ferrite. A low amount of boron can significantly improve the hardenability of steel. However, a high amount of boron can lead to boron embrittlement, which is detrimental to performance. Therefore, the content of boron in this invention is set to 0.001~0.01%.
[0080] V: 0.05%~0.20%, V can form carbides with C, which, on the one hand, refine the grains by pinning the original austenite grain boundaries through uniform and fine precipitation, thus improving strength and toughness; on the other hand, its dispersed distribution in the matrix provides precipitation strengthening. Furthermore, V can precipitate in large quantities during the heating process of hot stamping, further consuming C in the matrix and promoting the formation of dislocation-type martensite, thereby further improving the toughness of the hot-stamped component. Therefore, the component described in this invention can contain at least 0.05% V. However, excessive V addition leads to a significant increase in cost; therefore, in this invention, the V content is controlled within the range of 0.05% to 0.20%.
[0081] P: 0~0.020% In steel, phosphorus (P) is an unavoidable impurity element. On the one hand, P, as a solid solution strengthening element, can relatively inexpensively improve the strength of steel plates. On the other hand, when the P content exceeds 0.0200%, P will segregate at grain boundaries, leading to significant adverse effects such as a decrease in toughness. Therefore, the upper limit of P content is no more than 0.020%, preferably no more than 0.010%. Optionally, considering that keeping the P content below 0.001% would increase smelting costs, the lower limit of P content can be no less than 0.001%, and optionally no less than 0.004%.
[0082] S: 0~0.010% Similar to phosphorus (P), sulfur (S) is an unavoidable impurity element in steel. It reacts with manganese (Mn) in the steel to form MnS, becoming inclusions in the steel. When the S content exceeds 0.010%, a large amount of MnS will significantly impair the ductility and toughness of the steel, leading to a deterioration in workability. Therefore, the upper limit of the S content is no more than 0.010%, preferably no more than 0.005%. Similarly, optionally, considering that keeping the S content below 0.0001% would increase smelting costs, the lower limit of the S content can be no less than 0.0001%, preferably no less than 0.0005%, and more preferably no less than 0.001%.
[0083] N: 0~0.010% Nitrogen (N) is an unavoidable impurity element in steel, especially for steel containing boron (B). Nitrogen combines with B, significantly reducing B's effect on improving hardenability. Therefore, it is necessary to minimize the N content. Thus, the N content in this invention is controlled to not exceed 0.010%. However, in industrial production, all N removal processes imply increased production costs. Therefore, considering production costs, the lower limit for N content can be no less than 0.0001%.
[0084] The remaining chemical composition of the hot stamping steel sheet according to an embodiment of the present invention may also be Fe and impurities.
[0085] The hot stamping steel sheet according to an embodiment of the present invention may also contain at least one of the following elements to replace a portion of Fe, and its content is 0 when the following optional elements are not contained.
[0086] Ni: 0~0.40% Ni is a hardenability-improving element, and it can also improve the low-temperature toughness of steel. Therefore, its lower limit value can be optionally set to 0.01%. F b-s With a factor coefficient of 1.3, the large addition of Ni will inevitably lead to an increase in alloy cost and result in... F b-s The concentration of Ni is increased. Therefore, the Ni content is set to no more than 0.40%.
[0087] Mo: 0~0.15% Mo can improve the hardenability of steel plates and prevent temper brittleness. Preferably, it can be added at 0.01% or more. However, excessive Mo addition will lead to the formation of a large number of carbides within the steel plate microstructure and their segregation at grain boundaries. F b-s The factor coefficient is 1.6, which is much higher than that of Mn. Therefore, excessive addition of Mo reduces the toughness of hot-stamped steel and increases costs. Therefore, the Mo content is set to be below 0.15%.
[0088] W: 0~0.20% The addition of W can significantly increase the strength of steel plates, and W-containing precipitates can serve as hydrogen capture sites; therefore, it is preferable to add more than 0.001%. However, W is a strong carbide-forming element, and when the W content exceeds 0.20%, coarse and unevenly distributed carbides will be formed, which will seriously impair the performance of hot-stamped components. Therefore, the W content is set to below 0.20%.
[0089] Cu: 0~0.20% Cu increases the hardenability of steel sheets, thereby improving the strength of hot-stamped components. To achieve this effect, the Cu content is preferably set to 0.001% or more. However, Cu tends to segregate at grain boundaries and form copper embrittlement, reducing the hot workability of the steel sheet; therefore, the Cu content is set to 0.20% or less.
[0090] Co: 0~0.50% The addition of Co can increase the martensitic transformation temperature, which is beneficial for the self-tempering of martensite and thus improves its toughness. Therefore, its lower limit can preferably be set to 0.01%. However, Co is a rare and valuable element, and excessive addition will increase the cost of steel sheets. Moreover, Co will promote the graphitization of carbon in steel, which will damage the toughness of hot-stamped components. Therefore, optionally, the Co content is set to 0.01% ≤ Co ≤ 0.50%.
[0091] Ti: 0~0.100%, Nb: 0~0.100% Ti and Nb form carbonitrides in steel, which enhance the strength of hot-stamped components through precipitation strengthening. To achieve this effect, the Ti and Nb contents are preferably set to 0.001% or more. Conversely, when the Ti content exceeds 0.100%, large-sized titanium nitrides are easily formed in the steel, reducing the toughness of the hot-stamped components. Furthermore, when the Nb content exceeds 0.100%, a large amount of carbonitrides are formed in the steel and segregate at grain boundaries, adversely affecting the toughness of the hot-stamped components. Therefore, the Ti and Nb contents are set to 0.100% or less. Optionally, 0.001% ≤ Ti + Nb ≤ 0.100%.
[0092] Ta: 0~0.10% Ta, as a strong carbide-forming element, can form stable carbides with C, thereby refining the grain size and enhancing the strength and toughness of the steel plate. Therefore, to achieve this effect, the Ta content is preferably not less than 0.001%. Furthermore, when the Ta content exceeds 0.10%, a large amount of carbides will precipitate and easily accumulate at grain boundaries, leading to a decrease in the toughness of the steel plate. Therefore, the Ta content is set to not exceed 0.10%.
[0093] Sn: 0~0.05% The addition of Sn can refine the grain size and improve the machinability of steel plates by combining with elements such as S. Preferably, the Sn content is not less than 0.001%. However, Sn tends to segregate at grain boundaries, increasing the brittleness of the steel. Therefore, the Sn content is set to not exceed 0.05%.
[0094] Sb: 0~0.05%, Sb also has the effect of refining grains, so to achieve this effect, the preferred Sb addition is not less than 0.001%. However, excessive segregation at grain boundaries can also have an adverse effect on the properties of steel, especially its plasticity and toughness, so the Sn content is set to not exceed 0.05%.
[0095] As: 0-0.05% As can strengthen steel to a certain extent, increasing its strength. However, as tends to accumulate at grain boundaries, leading to increased brittleness and deteriorated weldability. Therefore, the as content is set at 0 ≤ As ≤ 0.05%.
[0096] Mg: 0~0.010%, Ca: 0~0.010% Mg and Ca are commonly used for deoxidation during steel smelting and can also form sulfides with S, improving the quantity and morphology of inclusions in the steel sheet structure. Therefore, their addition amount is preferably not less than 0.001%. However, when the content of both Mg and Ca exceeds 0.010%, large-sized inclusions are formed in the steel sheet structure, damaging the toughness of hot-stamped components. Therefore, the content of Mg and Ca is set to not exceed 0.010%.
[0097] Zr: 0~0.10% Zr is a strong carbide-forming element, with effects similar to those of V, Nb, and Ti. Adding a small amount can refine the grain size and improve the low-temperature toughness of the steel plate. Preferably, the Zr content is not less than 0.001%. However, when the Zr content exceeds 0.10%, large-sized carbides form within the steel plate structure, leading to a decrease in the toughness of the hot-formed components. Therefore, the Zr content is set to 0 ≤ Zr ≤ 0.10%.
[0098] O: 0~0.02% O forms coarse oxides in steel, which is detrimental to the toughness of hot-stamped components. Therefore, a lower O content is preferred, and the O content should not exceed 0.02%, more preferably 0.006% or less.
[0099] REM: 0~0.05% REM (refined oxidizing agent) improves deformability and toughness of hot-stamped components by inhibiting oxide formation. To achieve this effect, the REM content is preferably set to 0.001% or more. However, the REM content should be controlled to not exceed 0.05% to avoid the formation of coarse oxides. In this invention, REM refers to a total of 17 elements including Sc, Y, and La series elements, and the REM content refers to the total content of these elements.
[0100] Optionally, 0 ≤ Mo + W + Cu + Co + Sn + Sb + Ca + Mg + Zr + REM ≤ 0.30% Elements such as Mo and W can improve the hardenability of steel, but the addition of these alloying elements increases the cost of the alloy. Therefore, they should only be added in appropriate amounts to the material. Meanwhile, Mo can combine with Cr and V to form composite precipitates, consuming the carbon element in the matrix and playing a role in precipitation strengthening and improving the toughness of the martensitic matrix. Therefore, considering the economic efficiency of the material alloy, the total amount of the above alloying elements should be controlled to not exceed 0.30%.
[0101] It should be noted that in the steel sheet of the embodiments of the present invention, the remaining portion other than the components described above consists of Fe and impurities. Impurities are components that are mixed in during the industrial manufacturing of steel sheets using raw materials such as ores and scrap iron, and include substances that are not intentionally added relative to the steel sheet of the embodiments of the present invention (so-called unavoidable impurities). Furthermore, impurities are elements other than the components described above, and also include elements contained in the steel sheet at a level that does not affect the characteristics of the steel sheet of the embodiments of the present invention due to the unique effects of that element. For example, sometimes unavoidable impurity elements such as As are mixed in from scrap, but if it is within the normal range, it will not affect the characteristics of the steel sheet matrix of the hot-stamped steel sheet.
[0102] The chemical composition of the aforementioned hot-stamped steel sheet and hot-stamped components can be determined using general analytical methods. For example, it can be determined using ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). If the surface of the hot-stamped component has a coating or paint film, the chemical composition can be analyzed after removing the coating or paint film by mechanical grinding.
[0103] To ensure that hot-stamped components achieve a tensile strength of over 1950 MPa while also possessing good toughness, the inventors proposed simultaneously controlling the banded structure sensitivity factor 1.4Mn+1.1Cr+1.4Si+1.3Ni+1.6Mo-0.78Al and the austenite pre-strain critical cooling rate stability factor during alloy design. F pre-strain =C+2.1(Mn+1.29Cr+0.07Si+0.37Ni+3.28Mo)+0.5Al. The two compounds work synergistically to adjust the alloy composition, thereby achieving sufficient hardenability to ensure the strength of the hot-stamped components and reducing banded segregation to ensure the toughness of the hot-stamped components.
[0104] Specifically, to control the formation of banded structures, the inventors did not use conventional methods such as high-temperature homogenization annealing, but instead proposed controlling the amount of alloying elements added, especially those prone to segregation, by controlling the banded structure sensitivity factor. F b-s The size of the tissue is adjusted to improve its uniformity and thus achieve high toughness.
[0105] Meanwhile, the hardenability of the material, especially when high-temperature deformation is required, should be sufficient to ensure that the room-temperature microstructure of the hot-stamped component matrix is primarily martensitic. According to common knowledge, to ensure this hardenability, a large amount of alloying elements needs to be added, which contradicts the desire to reduce banding, making it difficult to simultaneously achieve high strength and high toughness. In contrast, the inventors have creatively discovered that when the carbon content is above 0.360%, while ensuring strength, carbon will also diffuse to dislocations during high-temperature hot stamping and produce a pinning effect, thereby inhibiting the transformation of austenite to ferrite (carbon diffusion-controlled phase transformation). This, in turn, suppresses the increase in the critical cooling rate of the material caused by pre-deformation, thus ensuring the material's hardenability without adding large amounts of elements such as Mn, Si, Cr, and Ni to improve hardenability. Therefore, the hot-stamped steel of the present invention does not need to follow the traditional hot-stamping alloy design when designing the alloy; meeting the following requirements is sufficient to ensure that the material has suitable hardenability.
[0106] Considering the above two aspects, and taking into account that the Mn content can decrease accordingly with the increase of C content, the present invention requires (1) when 0.360% ≤ C ≤ At 0.420%, 0.50% ≤ Mn≤1.20%, F b-s ≤2.65 and F b-s ≤9.05-16.92C and Fpre-strain ≥2.70; (2) when 0.420% <C ≤ At 0.480%, 0.20% ≤ Mn ≤ 0.50%, F b-s ≤1.75 and F b-s ≤18.43-36.15C and F pre-strain ≥2.40.
[0107] Optionally, in order to solve the problems encountered in rolling production, this invention proposes a hot-rolled and continuously annealed performance alloying factor. F pro =2.1Mn + 1.7Cr + 1.2Ni + 1.1Si + C + 0.9Al. The addition of high-content alloying elements increases the risk of elemental segregation within the microstructure and significantly improves the hardenability of the material, affecting the occurrence of phase transformations in various production processes. Therefore, in the hot rolling coiling process of industrial production, the head, tail, and edges of the coil, which are in contact with the outside environment, cool relatively quickly and are prone to forming a high proportion of hard martensite in their microstructure. Other parts are mainly composed of ferrite and pearlite. The difference in microstructure leads to uneven distribution of the overall properties of the hot-rolled coil, causing subsequent production problems such as difficulty in uncoiling, poor rolled sheet shape, and edge rolling cracking. Therefore, considering the influence of high-alloying element addition on the phase transformation of the microstructure during production, the inventors propose a 0.360%... ≤ C ≤ At 0.420%, control F pro =2.1Mn + 1.7Cr + 1.2Ni + 1.1Si + C + 0.9Al ≤ 3.7; and when 0.420% <C ≤ At 0.480%, control F pro ≤3.2, thereby controlling the phase transformation at the head and tail of the steel coil during hot rolling and coiling where cooling is too rapid, promoting the transformation of austenite into ferrite / pearlite and other structures as much as possible during the cooling process, ensuring the uniformity of the coil structure, thereby reducing defects such as poor flatness at the head and tail of the coil and cracking at the edge of the coil during subsequent rolling, which helps to obtain stable and controllable microstructure and mechanical properties in subsequent production and improve the yield of the product.
[0108] The present invention will now be described in more detail with reference to exemplary embodiments. The following examples or experimental data are intended to illustrate the present invention, and those skilled in the art should understand that the present invention is not limited to these examples or experimental data. The method for manufacturing a steel sheet according to an embodiment of the present invention uses materials within the above-described composition range and undergoes hot rolling and cold rolling and / or coating and annealing processes. Hereinafter, an example of a method for manufacturing a hot-stamped steel sheet according to an embodiment of the present invention will be described, but it will be understood that the method for manufacturing a hot-stamped steel sheet of the present invention is not limited to the following methods.
[0109] Prepare materials with the compositions shown in Tables 1 and 2, and process them into steel plates using the following process: a) Steelmaking: Steelmaking is carried out by vacuum induction furnace, electric furnace or converter according to the composition in Table 1 and Table 2, and billets are produced by continuous casting technology or by directly using thin slab continuous casting and rolling process. b) Hot rolling: The steel billet is heated to 1200℃ and held for 1 hour, then hot rolled at 800℃~1200℃, and coiled at 500~650℃ to form a hot-rolled steel coil. c) Cold rolling: The hot-rolled coil is pickled to remove the oxide scale generated during the hot rolling process, and then cold-rolled with a reduction of 30% to 70% to obtain a cold-rolled steel coil with a thickness of 1.0 to 2.0 mm.
[0110] Optionally, hot-dip galvanizing can be performed after cold rolling: a hot-dip aluminum-silicon pre-coating is applied to the cold-rolled steel sample, wherein the composition of the plating bath includes, by mass percentage: 9-12% Si, 2-3% Fe, and the balance being Al and impurities; the plating bath temperature is maintained at 630-670℃; and the single-sided coating weight is 20-75 g / m². 2 This step was performed on steel sheets C1 and S7 to exemplarily assess the degree of segregation in the steel sheet matrix. Alternatively, annealing can be performed after cold rolling to obtain the final steel sheet. It will be understood that other pre-coatings, such as zinc alloy pre-coatings, can also be applied to the cold-rolled sheet.
[0111] Table 1 Chemical composition of the steel plate matrix (%, balance is Fe and impurities) for each 2200 MPa grade steel plate
[0112] Table 2 Chemical composition of the steel plate matrix (%, balance is Fe and impurities) for each 2400 MPa grade steel plate
[0113] In subsequent experiments, the thickness of the experimental steel plates used was 1.4 mm. S1-S13 and HS1-HS10 are embodiments of the present invention, while C1-C7 and HC1-HC3 are comparative examples. Fb-s , F pre-strain and F pro It is calculated according to formulas 1-3 of the present invention.
[0114] According to GB / T 34474.1-2017, samples are taken at multiple locations along the rolling direction from each obtained steel plate. Then, the degree of banding is evaluated for each steel plate sample. Specifically, for each sample, a metallographic sample is prepared from a cross-section coplanar in the thickness and rolling directions according to the standard. Then, photographs are taken at at least three locations on the cross-section using an optical microscope, and the photographs are compared with a standard rating chart.
[0115] As an example, Figure 1A and Figure 1B The microstructure and corresponding standard rating spectra of the steel substrate samples of the obtained aluminum-silicon pre-coated steel plates C1 and S7 are shown. Figure 1A As shown, the segregation degree of the microstructure of steel plate C1 is similar to the banded distribution of grade 3 in the D series of the standard rating chart, therefore it is classified as grade 3D. Figure 1B As shown, steel plate S7 exhibits significantly less segregation, falling between grades 1 and 2 of the D series; therefore, it is classified as grade 1.5D. All other steel plate samples show varying degrees of segregation, with the degree of segregation increasing with... F b-s The increase exacerbates the situation. For 0.360% ≤ C ≤ 0.420%, when F b-s When it exceeds 2.68, and for 0.420% <C ≤ 0.480%, F b-s When the value exceeds 1.80, the microstructure of the sample exhibits severe segregation. For example, the segregation degree of HC1 and HC2 reaches level 3E, which is the level of segregation that this invention intends to avoid. In contrast, this invention requires that the room temperature microstructure of the steel plate matrix does not exceed level 2D or 2E, and therefore requires overall (1) 0.360%. ≤ C ≤ 0.420%, F b-s ≤ 2.65; (2) 0.420% <C ≤ 0.480%, F b-s ≤ 1.75.
[0116] Hardenability assessment experiment To evaluate the hardenability of the hot stamping steel sheet of the present invention, the most widely used hot stamping steel sheet, 22MnB5, was used as a benchmark. Its hardenability meets the requirements of current industrial production. Therefore, if the steel sheet of the present invention performs better than it, it also meets the hardenability requirements. The specific hardenability evaluation experiment is as follows: On a DIL805A / D phase transformation instrument, the tensile specimens of each steel sheet were heated to 930°C at 10°C / s and held for 3 min. Then, they were cooled to 600~700°C at a cooling rate of 20°C / s and subjected to isothermal stretching with a deformation of 10% at a deformation rate of 1 mm / s. After deformation, they were cooled to room temperature at a cooling rate of 30~50°C / s.
[0117] For example, Figures 2-3 Metallographic images of the room-temperature microstructure of the tensile portions of steel plates S3 (2200 MPa grade) and the known 22MnB5 (1500 MPa grade) after undergoing the same hardenability evaluation test according to an embodiment of the present invention are shown. The 22MnB5 has the following composition: 0.220% C, 1.20% Mn, 0.04% Ti, 0.16% Cr, 0.0025% B, 0.22% Si, 0.034% Al, with the balance being Fe and impurities. Figure 2 As shown, under 10% isothermal tensile deformation at 600°C, regardless of whether the cooling rate is 30°C / s or 50°C / s after deformation, the room temperature microstructure of 22MnB5, while predominantly martensite, contains a significant amount of ferrite, as indicated by the white areas pointed to by the arrows in the figure. In particular, it can be noted that the room temperature microstructure of 22MnB5 includes more ferrite at a cooling rate of 30°C / s compared to 50°C / s. This is because, as discussed earlier, deformation increases the driving force for the austenite-to-ferrite transformation, thereby accelerating ferrite formation. Therefore, a higher cooling rate is required to reduce this phase transformation. This is consistent with conventional understanding and is the reason why more alloying elements are typically added to improve hardenability when designing hot-stamped steels.
[0118] In contrast, the steel plate S3 according to an embodiment of the present invention, after undergoing a 10% deformation, exhibits a room temperature microstructure primarily composed of martensite, including very little ferrite. Even at a cooling rate of 30°C / s, the ferrite content in its room temperature microstructure is significantly less than that of 22MnB5 at a cooling rate of 50°C / s, demonstrating superior hardenability compared to 22MnB5. The steel plate S3 according to an embodiment of the present invention shows similar results when subjected to a 10% isothermal tensile deformation at 700°C, such as... Figure 3 The metallographic diagram is shown.
[0119] Figures 4-5Metallographic images of the room-temperature microstructures of the tensile portions of steel plates HS4 (2400 MPa grade) and the known 22MnB5, after undergoing the same hardenability evaluation test according to an embodiment of the present invention, are shown. Figure 4 The result is based on a 10% isothermal tensile deformation at 600°C. Figure 5 The results are for a 10% isothermal tensile deformation at 700°C. Similarly, regardless of whether it is an isothermal stretch at 600°C or 700°C, compared to 22MnB5, the room temperature microstructure of the example steel plate HS4 of the present invention, after undergoing a 10% deformation, is mainly martensitic with only a small amount of ferrite. Even at a cooling rate of 30°C / s, the ferrite content in the room temperature microstructure of the example steel plate HS4 of the present invention is less than that in the room temperature microstructure of 22MnB5 at a cooling rate of 50°C / s, demonstrating excellent hardenability.
[0120] These results demonstrate that, for the hot-stamping steel sheet of the present invention with high C content, sufficient martensitic structure can be obtained while maintaining hardenability without meeting the critical cooling rate of less than or equal to 20°C / s as commonly known. Therefore, it is not necessary to add a large amount of alloying elements to improve hardenability according to the design concept of less than or equal to 20°C / s. As discussed above, the reason why the example steel sheet of the present invention can maintain excellent hardenability at a cooling rate of 30°C / s after 10% deformation is that the high C content can interact with dislocations during deformation, thereby suppressing the austenite-to-ferrite phase transformation and ensuring the formation of sufficient martensite. Without realizing this, those skilled in the art would generally not reduce the addition of alloys to ensure hardenability, especially considering the hardenability results of 22MnB5.
[0121] Performance testing of hot stamped components Hot-stamped specimens with dimensions of 65*210 mm were prepared from the 2200 MPa and 2400 MPa grade steel plates of the embodiments and the comparative steel plates of the present invention, respectively, and hot-stamping tests were conducted as follows: Each steel plate sample was placed in a heating furnace with an adjustable protective atmosphere at a temperature of 850~950℃ for 3~10 min. Then, the steel plate sample was transferred to the forming mold within 5~12 s, ensuring that the temperature of the steel plate sample was not lower than 750℃ when it was placed on the mold. Then, it was pressure-quenched to below 200℃, and then removed from the mold and cooled to room temperature to obtain the corresponding flat hot stamping forming component. Both surfaces of steel plate S11 and steel plate HS7 have aluminum-silicon pre-coating layers. The average thickness of the coating on one side after hot stamping is 18.3 μm and 17.5 μm, respectively. The other steel plate surfaces have no coating.
[0122] Subsequently, several samples were randomly selected from non-edge locations of a portion of the specimens and recorded as hot-stamped samples.
[0123] For another group of samples, to simulate the painting and baking process of automotive parts, they were tempered. The tempering process was based on the actual baking process, and was set to 170℃ for 20 minutes. Afterwards, several samples were randomly selected from the non-edge positions of the baked samples and recorded as baked samples.
[0124] It will be understood that the method for manufacturing hot-stamped components using the hot-stamped steel sheet of the present invention is not limited to the above. Knowing the expected performance, those skilled in the art can select an appropriate production method from conventional methods as needed. For example, to soften the material, tempering can be performed at 130 to 300°C after hot stamping; the baking process can be set to hold at 150 to 200°C for 20 to 30 minutes, etc.
[0125] For each example hot-stamped steel plate sample, metallographic samples were prepared from cross-sections coplanar in the thickness and rolling directions. The microstructure was then observed and hardness measured under an optical microscope. Hardness testing method: Using a FALCON 501FAP from Yinuo Instruments, a 12*5 array hardness test was performed along the thickness direction on the cross-section of each hot-stamped sample. The test force was 300 g, and the average hardness was taken at five points along the rolling direction to assess the segregation within the microstructure after hot stamping in the thickness direction (illustrated by...). Figure 6 Sample S7 in the image shows the test conditions. Figure 6 The room temperature microstructure of a hot-stamped component specimen made of steel plates C1 and S7 is shown in the thickness direction, showing the hardness distribution.
[0126] In addition, according to GB / T 228.1-2010 Metallic Materials - Tensile Testing - Part 1: Test at Room Temperature (using P5 specimens, L0=50 mm, b0=12.5 mm) and the VDA-238 three-point bending standard, the yield strength, tensile strength, uniform elongation, and VDA bending angle were tested. To facilitate sampling from hot-stamped components, the specimen size could optionally be 60 mm × 30 mm. To reduce measurement error, all test results are averages of three sets of test results. Specific results are listed in Tables 3 and 4.
[0127] Planar fracture strain test Fracture strain is independent of material thickness and is an intrinsic property of the material in a planar state that characterizes the fracture limit (Cai, HL, Wang, JF, Wu, D., & Yi, HL (2021). A Simple Methodology to Determine Fracture Strain of Press-Hardened Steels Under Plane Strain Bending. Metallurgical and Materials Transactions A, 52(2), 644-654.). Therefore, considering that the VDA bending angle is affected by the thickness of the sheet metal, in order to more accurately characterize the toughness of the hot-stamped components made from the hot-stamped steel sheet of the present invention, the inventors tested the planar fracture strain of each obtained hot-stamped component. The specific test process is as follows: (1) Determine the VDA bending angle of the component specimen using the VDA cold bending test. α peak (2) Based on the experimental results, select at least three sets of interrupted bending angles. α L (i.e., the bending angle of the component specimen under load) An interrupted bending test is conducted to ensure... α L ≥50% α peak (3) When the component specimen is bent to α L When loading is stopped, the bending angle of the component specimen under unloaded condition is measured. α UL (4) Place the unloading component sample under an optical microscope and measure the inner and outer surface radii of the most severely deformed area. R i and R o (5) Calculate the different values according to equation (1). α UL The equivalent (plastic) strain on the outer surface of the most severely deformed zone of the component specimen under unloading conditions. ε That is, the component sample is bent to α L The equivalent strain of the outer surface of the most severely deformed zone of the component specimen was used to establish... ε - α L Relationship; (6) Based on the fitting results, the plane fracture strain of the component specimen is obtained by extrapolation (i.e., α L equal α peak time ε ): .
[0128] The specific results are listed in Tables 3 and 4.
[0129] Table 3 Performance test results of hot-stamped components with a strength of 2200 MPa
[0130] Table 4 Performance test results of hot-stamped components with a strength of 2400 MPa
[0131] As listed in Tables 3 and 4, the 2200 MPa-grade hot-stamped components S1-S13 according to the present invention all possess, in the hot-stamped state, a yield strength of not less than 1300 MPa (specific test results are in the range of 1322~1533 MPa), a tensile strength of not less than 2000 MPa (specific test results are in the range of 2032~2242 MPa), a uniform elongation of not less than 5.0% A%, and a VDA bending angle of not less than 40.0°. After baking, the yield strength is not less than 1500 MPa, and although the tensile strength decreases, it still remains not less than 1950 MPa, and the uniform elongation A% increases to not less than 5.8% and the VDA bending angle increases to at least 46.8°. Furthermore, the planar fracture strain of the hot-stamped components S1-S13 is not less than 0.170.
[0132] Similarly, the 2400 MPa-grade hot-stamped components HS1-HS10 according to the present invention all possess, in the hot-stamped state, a yield strength of not less than 1430 MPa (specific test results are in the range of 1434~1576 MPa), a tensile strength of not less than 2300 MPa (specific test results are in the range of 2302~2437 MPa), a uniform elongation A% of not less than 5.0%, and a VDA bending angle of not less than 33.0°. After baking, the yield strength is not less than 1600 MPa, the tensile strength decreases but still remains not less than 2150 MPa, and the uniform elongation A% increases to not less than 5.4%, and the VDA bending angle increases to at least 43.0°. Furthermore, the planar fracture strain of the hot-stamped components HS1-HS10 is not less than 0.110.
[0133] Regardless of whether it is at the 2200 MPa or 2400 MPa level, the example hot-stamped components S1-S13 and HS1-HS10 of this invention exhibit excellent high strength and high toughness. In particular, for the ultra-high strength component at the 2400 MPa level, its planar fracture strain is not less than 0.110, enabling the hot-stamped components to meet existing collision safety requirements with a thinner thickness, thereby reducing vehicle weight and improving cost-effectiveness.
[0134] F b-s Function First, for the 2200 MPa class, C1-C3 and C6 F b-s All values were greater than 2.65, and the corresponding VDA bending angles of the hot-stamped components failed to reach 46.0° after baking. The planar fracture strain was less than 0.170, failing to meet the toughness requirements. Therefore, this invention requires... F b-s ≤2.65, optionally, F b-s ≤2.60, optionally, F b-s ≤2.20, further optionally F b-s ≤1.80.
[0135] For the 2400 MPa level, C1-C2 F b-s All values were greater than 2.00, and the corresponding VDA bending angles failed to reach 43.0° after baking. The planar fracture strain was less than 0.110, failing to meet the toughness requirements. Referring to Example HS2 of this invention, this invention requires overall... F b-s ≤1.75, optional, F b-s ≤1.70, optional, F b-s ≤1.65.
[0136] Furthermore, it is worth noting that F b-s The relationship with carbon content. For example, the carbon content of the matrix of a hot-stamped component C1 is 0.380%. Although its tensile strength is as high as 2085 MPa, its VDA bending angle is only 44.9° and its plane fracture strain is low. ε With a tensile strength of only 0.155, it does not meet the toughness requirements. In contrast, the hot-stamped component S7 with the same carbon content not only has a tensile strength as high as 2073 MPa and a VDA bending angle of 52.6°, but also a plane fracture strain. ε Up to 0.228. The main reasons for the difference in toughness between the two are as follows: Figure 6 As shown, a distinct hardness peak exists in the C1 matrix along the thickness direction. This is because C1... F b-s With a hardness as high as 2.76, severe segregation of alloying elements occurred during the rolling process (as shown in Figure 1), which remained in the hot stamping process. This resulted in the formation of high-carbon, high-alloy hard and brittle martensite during hot stamping, causing a significant increase in hardness in localized areas and a large hardness difference compared to the surrounding area. In contrast, the hardness distribution of the matrix of the hot-stamped component S7 is relatively gentle. This is because S7's... F b-s A value of 1.71 indicates that the steel plate exhibits reduced segregation relative to C1, which corresponds to the banded microstructure level shown in Figure 1. Therefore, during three-point bending and plane fracture strain tests, the hard and brittle martensite present in the microstructure of steel plate C1 after hot stamping, compared to steel plate S7, induces fracture earlier, making it difficult to achieve high VDA bending angles and high plane fracture strains. Therefore, it is desirable to reduce the banded microstructure sensitivity factor. F b-s To minimize or eliminate the formation of low-toughness martensite in the room-temperature microstructure of hot-stamped components, thereby improving the toughness of hot-stamped components.
[0137] The test results of other samples showed a similar trend, namely, at the same C content, with the increase of the band tissue sensitive factor... F b-s As the carbon content increases, the VDA angle and plane fracture strain of the hot-stamped component specimens decrease. For example, hot-stamped components C4, S13, S6, and S4 all have a carbon content of 0.365%, but the corresponding... F b-s The values gradually increased, reaching 1.01, 1.80, 1.81, and 2.60 respectively. Correspondingly, the VDA bending angle showed a decreasing trend, reaching 60.9°, 52.9°, 52.1°, and 47.9° respectively, and the plane fracture strain also showed a decreasing trend, reaching 0.295, 0.232, 0.223, and 0.182 respectively. For example, S2, S7, and C1... F b-s The VDA bending angle and plane fracture strain exhibit the same variation pattern. This pattern also applies to the test results of hot-stamped components at the 2400 MPa level, such as those exhibited by hot-stamped components HS3, HS4, and HC1. In other words, at the same C content, adjusting alloying elements can reduce... F b-s This can further reduce the formation of banded structures, thereby increasing the VDA bending angle and planar fracture strain of hot-stamped components.
[0138] On the other hand, for example, as exhibited by hot-stamped component S5 (0.372%C) and hot-stamped component S8 (0.397%C), in similar... F b-s With increasing C content, the VDA angle decreases and the planar fracture strain also decreases (the planar fracture strain of S5 is 0.240, and that of S8 is 0.201). This rule also applies to the 2400MPa grade hot-stamped components according to the present invention, such as hot-stamped components HS1 and HS10. That is, under the same conditions... F b-s In this case, the reduction in C content will also reduce the enrichment of C in martensite caused by segregation, and the toughness of martensite will be improved compared with the high C case. Consequently, the VDA bending angle and planar fracture strain of the hot stamped component will be improved accordingly.
[0139] Figure 7A and Figure 7B The C content at 2200 MPa and 2400 MPa levels are shown respectively. F b-s The relationship diagram shows that some of the data has been fitted.
[0140] In combination with the above, for F b-s Based on the discussion of C content and the performance results in Tables 3 and 4, for hot-stamped components of the 2200 MPa grade, in order to ensure that the VDA bending angle is not less than 45.0° or the plane fracture strain is not less than 0.170, the following requirements are made: F b-s ≤2.65, optional F b-s ≤2.60 and F b-s ≤9.05-16.92C; preferably, in order to ensure that the VDA bending angle is not less than 50.0° or the plane fracture strain is not less than 0.190, it is required that... F b-s ≤8.55-16.92C; More preferably, in order to ensure that the VDA bending angle is not less than 52.0° or the plane fracture strain is not less than 0.220, it is required that... F b-s ≤8.05-16.92C.
[0141] For hot-stamped components with a strength of 2400 MPa, in order to ensure that the VDA bending angle is not less than 43.0° or the plane fracture strain is not less than 0.110, the following requirements must be met. F b-s ≤1.75 and F b-s≤18.43-36.15C; preferably, in order to ensure that the VDA bending angle is not less than 45.0° or the plane fracture strain is not less than 0.118, it is required that... F b-s ≤17.563-36.15C.
[0142] It is worth noting that, for the 2200 MPa level, although the point values of comparative examples C5 and C7 fall within the range mentioned above... F b-s Within the region defined by the relationship with C, this merely indicates that its banded structure sensitivity factor meets the above requirements. Considering that the tensile strength of the hot-stamped component made from steel plate C5 does not meet the expected requirements, and the Al content of steel plate C7 is far outside the scope claimed by this invention, comparative examples C5 and C7 are directly excluded from the above range by other limitations. Similarly, comparative example HC3 of the 2400 MPa grade is also directly excluded.
[0143] F pre-strain Function Through extensive experimentation, the inventors discovered that, in order to ensure sufficient martensite in the room-temperature microstructure of hot-stamped components to achieve the desired high strength, for 2200 MPa grade steel plates, F pre-strain It must be no less than 2.70; for 2400 MPa grade steel plates, F pre-strain The tensile strength must be no less than 2.40. If this condition is not met, the expected strength cannot be achieved. For example, although the baked VDA bending angle of a C4 hot-stamped component is as high as 60.9° and the plane fracture strain is as high as 0.295, the tensile strength of the hot-stamped C4 component is only 1888 MPa, which does not meet the expected requirement of 1950 MPa. This is because its... F pre-strain With a tensile strength of only 2.04, it is insufficient to generate enough martensite to improve the tensile strength of the hot-stamped component, thus failing to meet the requirements for both high strength and high toughness. Correspondingly, the tensile strength of the hot-stamped component HC3 did not reach 2150 MPa, failing to meet the high strength requirement.
[0144] Furthermore, at the same C content, it can be improved by increasing... F pre-strain This improves the tensile strength to a certain extent, as seen in the strength results of hot-stamped components S4 and S13, and hot-stamped components HS5 and HS9. Therefore, under the same C content, it is possible to increase the tensile strength by increasing... F pre-strain This can improve tensile strength to a certain extent. Given that hardenability is already guaranteed, the room temperature microstructure of the component matrix is almost entirely martensitic, making...F pre-strain Further increases would have limited effect on strength.
[0145] F b-s and F pre-strain Synergistic effect It is worth noting that, F pre-strain Increasing the alloy content means increasing the amount of alloy, which in turn leads to increased segregation. This is detrimental to achieving high VDA angle and plane fracture strain, i.e., high toughness. Therefore, in order to ensure that hot-stamped components possess both high strength and high toughness, the alloy elements must be considered simultaneously when designing the alloy. F b-s and F pre-strain Both must meet their requirements; otherwise, the strength will be insufficient, the VDA bending angle will be too small, and / or the plane fracture strain will be insufficient.
[0146] The experimental results of hot-stamped components C1-C4, C6, and HC1-HC3 verify that in order to achieve high strength and high toughness in hot-stamped components, the following conditions must be met simultaneously: F b-s and F pre-strain The necessity of this invention. This invention requires that, for hot-stamped components of the 2200MPa grade, in order to ensure a tensile strength of not less than 1950 MPa, a VDA bending angle of not less than 45.0°, or a plane fracture strain of not less than 0.170, the following requirements must be met: F b-s ≤2.65, optional F b-s ≤2.60, and F b-s ≤9.05-16.92C and F pre-strain ≥2.70; preferably, in order to ensure that the VDA bending angle is not less than 50.0° or the plane fracture strain is not less than 0.190, it is required that F b-s ≤8.55-16.92C; More preferably, in order to ensure that the VDA bending angle is not less than 52.0° or the plane fracture strain is not less than 0.220, it is required that... F b-s ≤8.05-16.92C.
[0147] For hot-stamped components with a strength of 2400 MPa, in order to ensure that the VDA bending angle is not less than 43.0° or the plane fracture strain is not less than 0.110, the following requirements must be met. F b-s ≤1.75, optional F b-s ≤1.70, and F b-s≤18.43-36.15C and F pre-strain ≥2.40; Preferably, in order to ensure that the VDA bending angle after baking is not less than 45.0°, or the plane fracture strain is not less than 0.118, it is required that... F b-s ≤17.563-36.15°C. Optionally, F b-s ≤1.65.
[0148] F pro Function As listed in Tables 3 and 4, defects such as poor flatness at the beginning and end of the cold-rolled coil and high rolling force existed during the sample production process, for example, S1-S4 and HS1 and HS2. To eliminate this phenomenon and ensure the continuous stability of steel coil production and obtain hot-rolled coils with high stability in both microstructure and properties, this invention further proposes a method at 0.360%. ≤ C ≤ At 0.420%, regulation F pro =2.1Mn+1.7Cr+1.2Ni+1.1Si+C+0.9Al≤3.7, optionally F pro ≤3.5; and when 0.420% <C ≤ At 0.480%, regulation F pro ≤3.2, optional F pro With a content of ≤2.9, the formation of a high proportion of martensite in the steel plate matrix during continuous cooling in the production process is greatly reduced or avoided. Instead, a microstructure dominated by ferrite and pearlite is obtained, which reduces or at least alleviates defects such as edge cracking and poor flatness after cold rolling of coil heads and tails, thereby improving the yield of hot stamping steel products.
[0149] The role of Al / C Steel plates S6 and C7 have essentially the same elemental content, except that S6 has an Al content of 0.35%, which is ten times that of C7. By adding a large amount of Al, the VDA bending angle of the hot-stamped component made from steel plate S6 is approximately 52.1°, an increase of approximately 12.5% compared to the hot-stamped component made from steel plate C7. Similarly, the planar fracture strain of the hot-stamped component made from steel plate S6 is increased by as much as approximately 32.7% compared to the hot-stamped component made from C7. This is because Al atoms have a larger atomic size than Fe atoms and are substitutional solid solution atoms. Therefore, when a large amount of Al is added, the corresponding lattice expands, and the lattice constant increases. Even with similar degrees of segregation resulting in the same degree of C enrichment, by optimizing the ratio of Al to C additions, the degree of martensitic lattice distortion caused by interstitial solid solution C atoms in the high-C content steel plate matrix is significantly reduced, improving the toughness of the martensite and thus enabling the steel plate to achieve higher toughness.
[0150] Furthermore, compared to steel plate S6, steel plate S13, with the same C content, achieves a VDA bending angle of nearly 53.0° and a plane fracture strain of 0.232 by having a higher Al content (0.50%), further improving the toughness of the hot-stamped component. In other words, with the same C content, adding more Al can further optimize the VDA bending toughness or plane fracture strain. Therefore, this invention requires Al / C ≥ 0.65, optionally Al / C ≥ 0.90, and more optionally Al / C ≥ 1.1.
[0151] In summary, the hot-stamped components made from the hot-stamping steel sheet according to the present invention possess high strength and high toughness, enabling existing collision safety requirements to be met with thinner sheet thicknesses, thereby reducing vehicle weight. This helps reduce vehicle costs, improve fuel economy, reduce energy consumption and exhaust emissions, aligning with the lightweighting trend in the automotive industry.
[0152] The above embodiments and experimental data are intended to illustrate the present invention by way of example. Those skilled in the art should understand that the present invention is not limited to these embodiments, and various modifications can be made without departing from the scope of protection of the present invention.
Claims
1. A steel sheet for hot stamping, wherein the chemical composition of the steel sheet matrix comprises, by mass percentage: 0.360%≤C≤0.480%, 0.20%≤Mn≤1.20%, 0.10%≤Si≤0.80%, 0.10%≤Cr≤1.00%, 0.20%≤Al≤0.70%, 0.001%≤B≤0.010%, 0.05%≤V≤0.20%, 0≤Ni≤0.40%, 0≤P≤0.020%, 0≤N≤0.010%, 0≤S≤0.010%, 0≤Mo≤0.15%, 0≤W ≤0.20%, 0≤Cu≤0.20%, 0≤Co≤0.50%, 0≤Ti≤0.100%, 0≤Nb≤0.100%, 0≤Ta≤0.10%, 0≤Sn≤0.05%, 0≤Sb≤0.05%, 0≤As≤0.05%, 0≤Mg≤0.010%, 0≤Ca≤0.010%, 0≤Zr≤0.10%, 0≤O≤0.02%, and 0≤REM≤0.05%, with the balance being Fe and impurities; Among them, the banded structure sensitivity factor of the steel plate matrix F b-s and austenite pre-strain critical cooling rate stability factor F pre-strain The following conditions must be met: (1) When 0.360% ≤ C ≤ At 0.420%, 0.50% ≤ Mn≤1.20%, F b-s ≤2.65 and F b-s ≤9.05-16.92C and F pre-strain ≥2.70; (2) When 0.420% <C ≤ At 0.480%, 0.20% ≤ Mn ≤ 0.50%, F b-s ≤1.75 and F b-s ≤18.43-36.15C and F pre-strain ≥2.40; in, F b-s =1.4Mn+1.1Cr+1.4Si+1.3Ni+1.6Mo-0.78Al, F pre-strain =C+2.1(Mn+1.29Cr+0.07Si+0.37Ni+3.28Mo)+0.5Al。 2. The steel sheet for hot stamping according to claim 1, wherein, When 0.360% ≤ C ≤ At 0.420%, F b-s ≤8.55-16.92C, optionally, F b-s ≤8.05-16.92C.
3. The steel sheet for hot stamping according to claim 1, wherein, When 0.360% ≤ C ≤ At 0.420%, F b-s ≤2.20, optional F b-s ≤1.
80.
4. The steel for hot stamping according to any one of claims 1 to 3, wherein, When 0.360% ≤ C ≤ When the content is 0.420%, 0.25%≤Al≤0.50% or 0.55%≤Mn≤1.00%.
5. The steel sheet for hot stamping according to claim 1, wherein, When 0.420% <C ≤ At 0.480%, F b-s ≤17.563-36.15C, optional F b-s ≤1.
70.
6. The steel sheet for hot stamping according to claim 5, wherein, 0.430% ≤ C ≤ 0.470%, or 0.45%≤Al≤0.65% or 0.25%≤Mn≤0.46%.
7. The hot-stamped steel sheet according to any one of claims 1-3 and 5-6, wherein, 0.25%≤Si≤0.70%, or 0.10%≤Cr≤0.85%.
8. The hot-stamped steel sheet according to any one of claims 1-3 and 5-6, wherein, The steel plate matrix comprises, by mass percentage, at least one of the following: 0.01%≤Ni≤0.40%, 0.01%≤Mo≤0.15%, 0.001%≤W≤0.20%, 0.001%≤Cu≤0.20%, 0.001%≤Co≤0.50%, 0.001%≤Ti+Nb≤0.100%, 0.001%≤Ta≤0.10%, 0.001%≤Sn≤0.05%, 0. 0.001%≤Sb≤0.05%, 0.001%≤As≤0.05%, 0.001%≤Mg≤0.010%, 0.001%≤Ca≤0.010%, 0.001%≤Zr≤0.10%, 0.001%≤O≤0.02%, and 0.001%≤REM≤0.05%, and 0.001%≤Mo+W+Cu+Co+Sn+Sb+Ca+Mg+Zr+REM≤0.30%.
9. The hot-stamped steel sheet according to any one of claims 1-3 and 5-6, wherein, The steel plate matrix comprises, by mass percentage: 0.360%≤C≤0.480%, 0.20%≤Mn≤1.20%, 0.10%≤Si≤0.80%, 0.10%≤Cr≤1.0%, 0.20%≤Al≤0.70%, 0.001%≤B≤0.010%, 0.05%≤V≤0.20%, 0≤Ni≤0.40%, 0≤Mo≤0.10%, 0.001%≤Ti+Nb≤0.100%, 0.001%≤P≤0.020%, 0.001%≤N≤0.010%, 0.001%≤S≤0.010%, with the balance being Fe and impurities.
10. The steel sheet for hot stamping according to any one of claims 1-3 and 5-6, wherein, The steel plate matrix comprises at least one of the following by mass percentage: 0.01%≤Ni+Mo≤0.40%, 0.001%≤Ti+Nb≤0.100%, and 0.15%≤Si≤0.65%.